2020
DOI: 10.1002/smll.202001626
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Capacity Negative Electrode for Asymmetric Supercapacitors Based on a PMo12 Coordination Polymer with Novel Water‐Assisted Proton Channels

Abstract: The development of a negative electrode for supercapacitors is a critical challenge for the next-generation of energy-storage devices. Herein, we describe two new electrodes formed by the coordination polymers [Ni(itmb) 4 (HPMo 12 O 40 )]•2H 2 O (1) and [Zn(itmb) 3 (H 2 O)(HPMo 12 O 40 )]•4H 2 O (2) (itmb = 1-(imidazo-1-ly)-4-(1,2,4-triazol-1-ylmethyl)benzene), synthesized by a simple hydrothermal method. Compounds 1 and 2 show high capacitances of 477.9 and 890.2 F g -1 , respectively. An asymmetric supercapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(70 citation statements)
references
References 67 publications
0
70
0
Order By: Relevance
“…In order to realize the charge balance between cathode and anode during the charge and discharge process, we have determined the mass ratios of cathode to anode at ≈ 1.2. According to CV curves at different scan rates, it is found that as‐assembled asymmetric device can operate efficiently within the voltage window range of 0–1.7 V. It should be noted that the voltage window in this work is twice that of traditional symmetrical supercapacitors and single‐electrodes in sulfuric acid electrolyte, [ 17 ] which also exceeds most of reported pseudocapacitive proton supercapacitors. [ 16,41,42 ] A pair of broad redox peaks appeared in the potential window of 0.6 V–1.7 V, indicating the Faradaic feature during proton storage procedure.…”
Section: Resultsmentioning
confidence: 76%
“…In order to realize the charge balance between cathode and anode during the charge and discharge process, we have determined the mass ratios of cathode to anode at ≈ 1.2. According to CV curves at different scan rates, it is found that as‐assembled asymmetric device can operate efficiently within the voltage window range of 0–1.7 V. It should be noted that the voltage window in this work is twice that of traditional symmetrical supercapacitors and single‐electrodes in sulfuric acid electrolyte, [ 17 ] which also exceeds most of reported pseudocapacitive proton supercapacitors. [ 16,41,42 ] A pair of broad redox peaks appeared in the potential window of 0.6 V–1.7 V, indicating the Faradaic feature during proton storage procedure.…”
Section: Resultsmentioning
confidence: 76%
“…Polyoxometalates (POMs) have intriguing structures and also could be a resource of metals. [ 200,201 ] Therefore, POMs‐based MOFs (POMOFs) can merge the advantages of MOFs and POMs and pass them onto derivatives materials that possess high surface areas, suitable paths for the electrons and ions, and rich defects which can enhance the electrochemical properties of the reaction. [ 202 ] Recently, Wang et al.…”
Section: Defect Engineering By Employing Mofsmentioning
confidence: 99%
“…In the {Co 2 L 3 •6H 2 O} + , two Co 2+ metals, three L − molecules and six water molecules (Figure 1, (Figure 1, middle). [54][55][56][57] Moreover, the {Co 2 L 3 •6H 2 O} + clusters and adjacent GeMo 12 polyanions are integrated together through massive hydrogen bond interactions ( Figure S3, Supporting Information) to fabricate a 3D supermolecular structure ( Figure 1).…”
Section: Characterizations Of Polymer Precursor and Cos 2 @Mos 2 @Ccmentioning
confidence: 99%